Ethnic Minority in the Perspective of Habitus: The Juncture of the ideas of Pierre Bourdieu and Rogers Brubaker - Stankevičienė, Evelina (Sociologija. Mintis ir veiksmas, 2004)
After the collapse of the Soviet bloc the regenerative specifics of the states was subject to a new outlook on nationalism of national minorities. Non-typical immigration process of the most national minorities in the regenerative countries does not enable from approaching them as typical groups of immigrants. In this article national minority is defined as a non-fixed, but changeable complex. Therefore, applying the method of theoretical analysis, there is an attempt to give a look to national minority as a dynamically changing field. The ideas of P.Bourdieu and R.Brubaker have been integrated trying to achieve this goal, which allowed forming national minority as a field of analytical model. Efforts were made to show that, due to this model, possibilities arise to single out more field actors than one homogenous group in the representation of national minority and present more flexible and universal analysis.
Keywords: ethnic minority; habitus; Pierre Bourdieu; Rogers Brubaker